Retarding strawberry fruit senesce with edible coatings : case study - Ribeiro, Clara (2005)
The objectives of this work were to study the ability of starch, carrageenan and chitosan based coatings to extend the shelf life of strawberry fruit (Fragaria ananassa). To do so, the surface properties of fresh strawberry and the wettability of the coatings were studied. The superficial tension of the strawberry was 28.94 mN/m, and its polar and dispersive component was 22.99 mN/m and 5.95 mN/m, respectively. The critical superficial tension of the strawberry was 18.84 mN/m, obtained from a Zisman plot. The wettability of the coatings (starch, carrageenan and chitosan) is optimized with compositions of, respectively: 2 % of starch and 2 % of sorbitol; 0,3 % of carrageenan, 0,75 % of glicerol and 0,02 % of Tween 80; 1 % of chitosan and 0,1 % of Tween 80. The effect of the application of these coatings in fresh strawberry was assessed by controlling the content in soluble solids, the colour evolution, the firmness, the mass variation and the microbiological growth during a period of 6 days. No significant differences were found between the chromaticity coordinates. The minimum loss of firmness was obtained in strawberries coated with carrageenan and calcium chloride. The minimum loss of mass was obtained in fruits with chitosan and carrageenan coatings both with calcium chloride. Relatively to the content in soluble solids the coating of chitosan and calcium chloride presented the best result. The addition of 1 % of di-hydrated calcium chloride to coatings was also studied, and this was shown to decrease the microbial growth rate of the fruit. The minimum rate of microbial growth was obtained with strawberries coated with chitosan and calcium chloride.